PERNIKAHAN DAN KELUARGA BERENCANA DALAM AL-QUR’AN - Saputro, Eko Andy; Afan, Suhaimi (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2021)
Islam recommends marriage for men who are able and willing to marry. Marriage is worship, because marriage will complete half of his religion. With a thematic approach, this article will discuss the nature of marriage according to the Koran and some issues related to family planning programs